Simple, Rapid and Sensitive UV-Visible Spectrophotometric Method for Determination of Antidepressant Amitriptyline in Pharmaceutical Dosage Forms - Pankaj Soni; Deepak Sinha; Rajmani Patel (Journal of Spectroscopy)
The paper describes a new and simple approach for spectrophotometric determination of tricyclic antidepressant drug amitriptyline. Enhancement of the colour intensity of the Fe(III)-SCN− complex on addition of the drug amitriptyline forms the basis of the proposed method. The value of molar absorptivity of the Fe(III)-SCN− amitriptyline ion pair complex in terms of the drug lies in the range of (2.82–3.36) × 103 L·mol−1·cm−1 at the absorption maximum 460 nm. The detection limit of the method was 0.3 μg·mL−1. The slope, intercept, and correlation coefficients for the present method were found to be 0.008, 0.002, and +0.998, respectively. The effect of analytical variables on the determination of the drug and the composition of the complex are discussed in the paper. The method is applicable in the determination of amitriptyline in pharmaceutical preparations.